The failure of supervisory stress testing: Fannie Mae, Freddie Mac, and OFHEO - W. Scott Frame; Kristopher Gerardi; Paul S. Willen (Federal Reserve Bank of Atlanta, 2015)
Stress testing has recently become a critical risk management and capital planning tool for large financial institutions and their supervisors around the world. However, the one prior U.S. experience tying stress test results to capital requirements was a spectacular failure: the Office of Federal Housing Enterprise Oversight's (OFHEO) risk-based capital stress test for Fannie Mae and Freddie Mac. We study a key component of OFHEOs model - 30-year fixed-rate mortgage performance - and find two key problems. First, OFHEO had left the model specification and associated parameters static for the entire time the rule was in force. Second, the house price stress scenario was insufficiently dire. We show how each problem resulted in a significant underprediction of mortgage credit losses and associated capital needs at Fannie Mae and Freddie Mac during the housing bust.
Keywords: G21; G23; G28; 330; Bank supervision; stress test; model risk; residential mortgages; government-sponsored enterprises